Case report: adenoid cystic carcinoma of the trachea mimicking bronchial asthma - K, Thanamogan.; Abdullah, Maizaton Atmadini; Salleh, Amizatul Aini; Mohamad Mokhtar, Elmina; Rajah, Rathika; Soo, Chun Ian (Semarak Ilmu Publishing, 2024)
We discussed a 54 years old Malay gentleman who presented to the emergency department with severe difficulty in breathing and wheezing. The patient almost collapsed and an emergency intubation was done followed by a CT scan of the neck and thorax later. CT scan showed an ill-defined heterogenously enhancing intramural lesion measuring 2.7 x 2.4 x 3.3 cm arising from the posterior tracheal wall and projecting into the tracheal lumen. A rigid bronchoscopy showed a polypoidal tumour mass at the lower one third of the trachea occluding the lumen. Partial resection of tumour and tracheal stenting were performed to relieve the obstruction. Histopathological examination of the resected sample showed a cellular tumour with cribriform pattern. The tumour composed of epithelial and myoepithelial cells. The cells displayed uniform basaloid to ovoid nuclei and scanty cytoplasm. Some of the epithelial cells showed mildly pleomorphic nuclei with prominent nucleoli. The cribriform pattern composed of predominantly myoepithelial cells with myxoid background or hyalinized globules. Mitotic figures were rarely seen. The stroma was hyalinized. A diagnosis of adenoid cystic carcinoma (ACC) was made.